Surface properties and wetting behavior of liquid Ag-Sb-Sn alloys - Sklyarchuk V.; Plevachuka Yu.; Kaban I.; Novakovic R. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Surface tension and density measurements of liquid Ag-Sb-Sn alloys were carried out over a wide temperature range by using the sessile drop method. The surface tension experimental data were analyzed by the Butler thermodynamic model in the regular solution approximation. The wetting characteristics of these alloys on Cu and Ni substrates have been also determined. The new experimental results were compared with the calculated values as well as with data available in the literature.